The Utility of ICD-11 and DSM-5 Traits for Differentiating Patients With Personality Disorders From Other Clinical Groups - Pires, Rute; Henriques-Calado, Joana; Sousa Ferreira, Ana; Bach, Bo; Paulino, Marco; Gama Marques, João; Ribeiro Moreira, Ana; Grácio, Jaime; Gonçalves, Bruno (Frontiers in Psychiatry, 2021)
The ICD-11 Classification of Personality Disorders delineates five trait domain qualifiers (i.e., negative affectivity, detachment, dissociality, disinhibition, and anankastia), whereas the DSM-5 Alternative Model of Personality Disorders (AMPD) also delineates a separate domain of psychoticism. These six combined traits do not only characterize individual stylistic features, but also the severity of their maladaptive expressions. It was therefore the aim of this study to investigate the utility of ICD-11 and DSM-5 trait domains to differentiate patients with personality disorders (PD) from patients with other mental disorders (non-PD). The Personality Inventory for DSM-5 Brief Form Plus (PID5BF+M) was administered to a sample of patients diagnosed with a personality disorder (N = 124, Mage = 42.21, 42.7% females) along with a sample of patients diagnosed with other mental disorders (N = 335, Mage = 44.83, 46.6% females). Group differences were explored using the independent sample t test or the Mann-Whitney U test for independent samples, and discriminant factor analysis was used to maximize group differences for each trait domain and facet score. The PD group showed significantly higher scores for the total PID5BF+M composite score, for the trait domains of negative affectivity, antagonism/dissociality, and disinhibition, and for the trait facets of emotional lability, manipulativeness, deceitfulness, and impulsivity. The trait domains of disinhibition, negative affectivity, and antagonism/dissociality as well as the trait facets of impulsivity, deceitfulness, emotional lability, and manipulativeness were the best discriminators between PD and non-PD patients. The global PID5BF+M composite score was also one of the best discriminators supporting its potential as a global severity index for detecting personality dysfunction. Despite some limitations, our findings suggest that the ICD-11 and DSM-5 traits have the potential to specifically describe the stylistic features that characterize individuals with personality disorders, including the severity of their maladaptive expressions.